Seed regeneration aided by nanomaterials in a climate change scenario: A comprehensive review - Chadha Utkarsh; Zablotny Kinga; Mallampati Aishwarya; Pawar Harshal Gopal; Batcha M. Asfer; Gokula Preethi S. K.; Arunchandra A. Naga Sai; Choudhury Moharana; Singh Bhanu Pratap (Nanotechnology Reviews)
Nanotechnology has demonstrated its potential for advancing sustainable agriculture. This article explores new advancements in nanotechnology in agriculture, including plant extraction and validation, by emphasizing nano-fertilizers, nano-pesticides, nano-biosensors, and nanoenergy recycling processes. Nanomaterials are important for the formation, transport, and degradation of soil toxins and are a fundamental starting point for various biotic and abiotic rehabilitation processes. Research on nanoparticles’ remediation applications and soil stay insufficient and are generally restricted. When integrated into agricultural systems, nanomaterials may influence the soil quality and plant development examined by setting their impacts on supplement discharge in target soils, soil biota, soil natural matter, and plant morphological and physiological reactions. The current research works show that the seed coat acts as a barrier to nanomaterial penetration, in which both the seed coat and cell wall allowed easy water passage. Additionally, the uptake, movement, and associated defense mechanisms of nanomaterials within plants have been investigated. Future research directions have been identified to further the study toward the sustainable development of nano-enabled agriculture.